Sikap Orang Tua Terhadap Penerimaan Konseling Genetika Pada Down Syndrome - Niken Safitri Dyan K; Costrie G. W; Sultana MH Faradz (Jurnal Keperawatan Anak, 2014)
Background: Genetics counseling can improve individual knowledge and decrease the level of anxiety. More information about genetic diseases received by individu will make them more comfortable because of the certainty. However, the low of public awareness and understanding of issues concerning the genetic disease resulted in the unrecognized the existence of genetic counseling. Research on how attitudes towards genetic counseling in families with Down syndrome child are felt necessary. This study aims to determine parents’ attitudes towards receiving genetic counseling of Down syndrome. Methods: A quantitative approach used questionnaire was applied cross-sectionally to parents of child with Down syndrome in one special school Semarang. Sample was determined by purposive sampling. Univariate and bivariate analysis were performed to analyze data. Results: A total of 51 respondents participated in this study. The results showed that the majority of respondents (84.3%) supported a genetic counseling session on Down syndrome. Most of the respondents (98.0%) had a positive attitude toward a child with Down syndrome. Based on the bivariate analysis, there was no significant difference (p-value = 0.416) between father and mother attitudes toward receiving genetic counseling of Down syndrome. Conclusion: Most of the respondents were interested in genetic counseling session although they did not know about it previously.